Youth entrepreneurship in agribusiness: Nigeria country report - Babu, Suresh Chandra; Zhou, Yuan; Koever, Lena; Srivastava, Nandita (Syngenta Foundation, 2020)
Promoting rural entrepreneurship is recognized as an effective way to increase youth engagement in economic activities and address rural unemployment. However, the ideal pre-conditions remain largely unresearched. All age-groups face certain recurring challenges associated with agriculture and agribusiness. These include access to technology, weather uncertainty, poor market linkages and price risks. For young people, these challenges are typically exacerbated by a lack of relevant skills and experience. Addressing these challenges requires answers to some key questions: Which factors drive the success of youth entrepreneurs in developing countries? What type of business ‘ecosystem’ is best suited for their development? What roles should the various stakeholders play in making youth entrepreneurship flourish nationally? How can young people expand their start-ups to become small, medium or large scale businesses? This report forms part of an international multi-country comparative study. It identifies key drivers for the success of youth entrepreneurship in Nigeria and examines challenges that the country’s youth face on their way to becoming successful entrepreneurs. The report starts with a review of literature on the status of rural youth entrepreneurship in Nigeria. Seven detailed case studies of rural and urban agribusiness youth entrepreneurs (YE) then highlight specific challenges and opportunities. The insights gathered help address key policy and programmatic gaps. They also enable us to offer recommendations for strengthening youth empowerment through entrepreneurial opportunities.